Exploring science competition participants' expectancy-value perceptions and identification: A latent profile analysis. (August 2021) - Steegh, Anneke; Höffler, Tim; Höft, Lars; Parchmann, Ilka
Abstract: Science competitions are positively linked to students' science career pursuit and admission at top universities. The search for effective gender equity measures has become a priority as girls are less successful during science Olympiad team selection. Based on the expectancy-value model we performed latent profile analysis on a dataset of 445 Chemistry Olympiad participants (51% female, mean age 16.50 years). We characterized motivational profiles, predicted profile membership using the gender-science Implicit Association Test, gender, and socializers' support, and examined how profile membership influenced performance. We identified four profiles distinguished by career motivation, interest, and domain identification: fearful pessimists, average participants, carefree participants, and worried optimists . The least successful group was associated with stronger gender-science stereotypes, less parental support, and the female gender. We discuss these findings in light of the importance of parental support and the diminishing effect of gender-science stereotypes on feelings of belonging for girls. Highlights: Four motivational profiles of science Olympiad participants were identified. The most successful profile was characterized by interest and career motivation. The least successful profile was strongest associated with the female gender. Weaker implicit gender stereotypes and more parental support were linked to success.